SUBSEQUENT PURIFICATION OF ARTIFICIAL SOLUTIONS OF PREGNANT LEACH SOLUTION OF MIXED HYDROXIDE PRECIPITATE (MHP) TO SYNTHESIZE HIGH-PURITY NICKEL SULFATE - Dhita Andriyanto, Visensius
In recent years, the battery industry for electric vehicles has increased significantly due to the issue of net zero emissions (NZE). The NZE issue encourages Indonesia to mine fossil energy sources in the transportation sector and make a transition to electric vehicles and has issued Presidential Regulation Number 55 of 2019 concerning the Acceleration of the Battery-Based Electric Motor Vehicle Program for road transportation. One of the most used electric vehicle batteries is a lithiumion battery whose cathode material is rich in nickel, namely the nickel-manganesecobalt oxide (NMC) type. NMC type lithium-ion batteries are widely used for electric cars because they have high energy density and are relatively safe. NMC battery cathodes in their manufacture require raw materials of nickel sulfate, manganese sulfate, cobalt sulfate, and lithium carbonate or lithium hydroxide. MHP is one of the sources of material to obtain nickel sulfate and cobalt sulfate products. In the process of refining MHP into nickel sulfate and cobalt sulfate, MHP is leached using sulfuric acid to produce a rich leach solution (pregnant leach solution, PLS) containing nickel, cobalt, and impurity metals such as Al, Zn, Mn, Mg, and Fe. To obtain high-purity nickel sulfate as a raw material for nickel-based battery cathodes, PLS must be purified and the most widely used method is the solvent extraction process (SX) using organic extractants that can separate impurity elements from Ni and Co and separate Ni from Co and the remaining impurity elements. The main impurities of MHP such as Fe, Al, and Zn can be separated from Ni using di(2-ethylhexyl) phosphoric acid (D2EHPA) extractant. Furthermore, bis(2,4,4- trimethylpentyl) phosphinic acid (Cyanex 272) extractant can separate Ni from Co, Mn, and Cu, while neodecanoic acid (Versatic 10) extractant can separate Ni from Mg to obtain a high purity nickel sulfate solution. This study aims to study the further purification of artificial solutions that simulate the leachate solution of MHP that has been purified with D2EHPA to synthesize high purity nickel sulfate. In the SX experiment with Cyanex 272, an artificial solution was used that simulated the MHP leaching solution after undergoing a purification process from Fe, Al, Zn, and Mn metals with SX using D2EHPA extractant. After the experiment iv with Cyanex 272 was completed, the experiment was continued with Versatic 10 to purify the nickel-rich solution. In the SX experiment with Versatic 10, an artificial solution was used that simulated the raffinate solution from the SX experiment with Cyanex 272 after Ni scrubbing. The diluent used in the SX experiment with both Cyanex 272 and Versatic 10 was kerosene. For each extraction experiment, tributyl phosphate (TBP) was added as much as 5% by volume as a phase modifier that prevents the formation of a third phase. The experimental variables studied in the extraction experiments with Cyanex 272 and Versatic 10 were equilibrium pH, extractant concentration, and the ratio of the volume of organic solution to the volume of aqueous solution (O/A ratio). The experimental variables studied in the Ni scrubbing experiment from loaded Cyanex 272 and Mg scrubbing from Versatic 10 were the initial pH and the O/A ratio. Meanwhile, the experimental variables studied in the Co stripping experiment from loaded Cyanex 272 and Ni stripping from loaded Versatic 10 were the concentration of sulfuric acid. The stripped liquor obtained was crystallized to obtain high-purity NiSO4•6H2O crystals. The results of the experiment showed that the extraction percentage of Ni, Mg, Co, Mn, and Cu tended to increase with increasing equilibrium pH, O/A ratio, and extractant concentration with Cyanex 272 and Versatic 10 extractants. The best extraction conditions with Cyanex 272 were obtained at equilibrium pH = 5, extractant concentration = 30% (v/v), and O/A ratio = 0.25 in 2 stages with Ni and Mg extraction percentages of 19.74% and 58.83% respectively and Co, Mn, and Cu extraction percentages approaching 100%. All Ni could be scrubbed at initial pH = 2 and O/A ratio = 1 in 1 stage with Mg and Co scrubbing percentages of 59.1% and 2.03% respectively, while Mn and Cu had not been scrubbed. The metal that is still in the organic phase can be stripped entirely at an acid concentration of 0.1 M and an O/A ratio of 2 in 1 stage. In addition, the best extraction conditions with Versatic 10 were obtained at an equilibrium pH of 7, an extractant concentration of 30% (v/v), and an O/A ratio of 0.5 in 2 stages with a Ni extraction percentage approaching 100%, and Mg co-extracted at 3.61%. All Mg can be scrubbed at an initial pH of 2 and an O/A ratio of 2 in 1 stage with a Ni scrubbing percentage of 0.93%. The Ni metal that is still in the organic phase can be stripped entirely at an acid concentration of 1 M and an O/A ratio of 2 in 1 stage. The stripped liquor from the entire process is then crystallized to obtain nickel sulfate crystals. The obtained crystals were digested and the Ni content was obtained at 22.15%, thus meeting the Ni content standard in battery grade nickel sulfate for NMC type lithium-ion battery cathode precursors.